Poplar based agroforestry systems: Intercropping of medicinal herbs for better production and diversification - Thakur, P.S.; Dutt, V.; Thakur, A.; Raina, R. (Indian Journal of Agroforestry, 2020)
This study was undertaken for two consecutive years during 2006 and 2007 with the objectives to find out the compatibility of medicinal and aromatic herb species for cultivation in association with poplar trees. Integration of medicinal and aromatic herb species namely, Digitalis lanata, Matricaria chamomilla and Salvia selaria with Populus deltoides, planted at 4 x 4 m on the farmland suggest better option for diversification of farming systems. The data obtained for growth, herb yield and physiological parameters of these medicinal and aromatic herb species indicated no substantial adverse impact of the presence of tree canopies on the growth and production potential. The application of fertilizers and farmyard manure to the medicinal herbs was found very useful for enhancing growth and production ability as well as photosynthetic efficiency of all the herb species. Nitrogen @ 100 kg/ha and FYM @ 4 t/ha in the presence as well as absence of poplar plantation proved most effective. Growth with respect to height, leaf number, spread, flower number, branch number and leaf area index, all index of better growth, was Significantly higher in fertilizer and FYM treated plots in comparison to control plots. Production increased with the use of fertilizers and FYM even in the presence of tree canopies.